Utility of a New Artificial Dermis as a Successful Tool in Face and Scalp Reconstruction for Skin Cancer: Analysis of the Efficacy, Safety, and Aesthetic Outcomes - Fedele Lembo; Liberato Roberto Cecchino; Domenico Parisi; Aurelio Portincasa (Dermatology Research and Practice)
Radical ablative surgery is the gold standard treatment of head skin cancer. The authors expose their experience with a new artificial dermis (Pelnac®), analyzing retrospectively the overall morbidity and aesthetic outcomes. 16 consecutive patients underwent two surgical procedures under local anesthesia. The first involved the tumor removal and application of the ADM. In the second, the exposed tissue was covered with a split-thickness skin graft. On follow-up (6 months), tumor recurrences, quality of scars (using the Vancouver Scar Scale), and patient reported outcomes (using FACE-Q Skin Cancer Module) were evaluated. 10 were males and 6 females, with a mean age of 73 years (61–89). The follow-up ranged from 12 to 48 months (mean: 30). The sites of skin tumor were scalp (12 cases), forehead (2), cheek (1), and zygomatic area (1). Nine patients underwent previous local surgery; two received radiotherapy. The average length of hospital stay was 3.2 days. The mean surface area of the defect was 59.15 cm2 (16.9–89.5). In three cases, the surgical bed was bone without periosteum. The malignant tumors excised were basal cell carcinoma (68.75%), squamous cell carcinoma (18.75%), malignant melanoma (6.25%), and sarcoma (6.25%). The mean operating time was 41 minutes for the first operation (25–55) and 34 for the second (25–48). No significant problems were observed and 15 patients (93.75%) had 100 percent intake of graft. The mean time of healing was 39 days (32–45). At 6 months post-op, no tumor recurrence. Satisfactory cosmetic and functional results were obtained in all patients as shown by the VSS Scale and FACEQ skin cancer module mean scores. We believe that the artificial dermis is a reliable alternative to flaps and should be considered an excellent option in head reconstruction for skin cancer, especially in critical patients (old, with large and deep defects, with recurrent tumors, required radiotherapy).